(3fXQjI GdJYSa aj GSJYeGd GdMbhb GdEOGQjI (B/s (3GdeLdO GdKGfjs - (3eMeO ejQZfi NjQi EOQjSs; (3SdjeGf eMeO GdWeGhjs; (3LGeYI Yjf TeSs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B- (3LGeYI Yjf TeS,s, 1972)
(3JbY fXQjI GdJYSa aj efWbI hSWj Hjf GdYed GdeTQhY hZjQ GdeTQhY (B, (3hjYJHQ GdbGfhf GdeOfj GdefHJ GdGUjd dfXQjI GdJYSa (B, (3hgfGc ENJdGa Hjf GdJYSa hGdGfMQGa GdPj jfOeL aj acQI YOe GdeTQhYjI (B, (3hjQj GdHGMK Cf GdbGVj jMce HGdJYSa HZjQ fU (B, (3hCMjGfG QZe Cfag (B, (3hjQj VQhQI GdOQGSGJ GdebGQfI Hjf aQhY GdbGfhf GdeNJdaI aj GdhWf GdhGMO hLhHG hVQhQI hGdJj JbY Ydj YGJb THGH GdHGMKjf GdPjf de jLQage JjGQ GdJNUU HYO(B.s
(3QSGFd fSNI efaQOIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI Yjf TeS, cdjI GdMbhb, bSe GdbGfhf GdYGe (B1972.s
(3HHdjhLQGajG(B: (3UaMGJ (B715- 736s
Keywords: (3GdbGfhf GdEOGQjs; (3GdJYhjV Ydi CSGS GdeNGWQs; (3bVGA GdZdhs; (3fXQjI ghQjhs; (3GdGfMQGa aj GSJYeGd GdSdWIs; (3fXQjI HhfGQs; (3fXQjI OjHhjgs; (3fXQjI GdJYSa HGdabg GdaQfSjs; (3fXQjI GdJYSa hfXQjI GdGfMQGas; (3QSGFd LGeYjIs -- (3LGeYI Yjf TeSs